Removal of High Concentration of H2S in an Airlift-Loop Reactor - Cheng, R.; Wei, Y.C.; Zhang, Y.K.; Liang, Y. (Asian Journal of Chemistry, 2010)
A type of airlift-loop reactor inoculated with Thiobacillus thioparus S1 was developed for treating a gaseous stream containing high concentrations of hydrogen sulfide. This result showed superior performance of the bioreactor for H2S removal. The bioreactor systems allowed an efficiency of 99 % when fed with 380-5400 ppmv H2S. And the maximum elimination capacity was about 235 g-H2S m-3 h-1. At high inlet concentration of 5120 ppmv, the conversion products were mainly sulfur and the production rate of SO4 2- was only 2.8 mg h-1. The biokinetic constants, Vm and Ks for the airlift-loop bioreactor were 277.8 g-H2S m-3 h-1 and 366.3 ppmv, respectively.